Lipid profile alterations and fasting blood glucose levels in primary hypothyroidism - Sushma, Maram; Ramalingam, Krishnan; Naidu, Jupalli N.; Lakshmi, Tatireddy V. (International Journal of Research in Medical Sciences, 2017)
Background: Hypothyroidism has become a highly prevalent condition worldwide as well as in India. Females are affected more than men and dyslipidemia has been associated with hypothyroidism. This study was conducted to study the prevalence and pattern of dyslipidemia in hypothyroid patients and to justify the screening of lipid profile in hypothyroid patients. Methods: This was a case control study which included 50 newly diagnosed and untreated hypothyroid patients and 50 healthy individuals in the age group of 20-40years. Free Triiodothyronine (FT3), free thyroxine (FT4), Thyroid Stimulating Hormone (TSH) were estimated by chemiluminiscence immunoassay.Serum total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), blood glucose were done in all the subjects by enzymatic colorimetric method. Low density lipoprotein cholesterol (LDL-C) was calculated using Friedwalds formula. Very Low density lipoprotein cholesterol (VLDL-C) was calculated from the triglyceride value. Results: Lipid profile alterations were seen in hypothyroid patients. The mean (standard deviation)values of Total cholesterol, high density lipoprotein cholesterol (HDL-C), Low density lipoprotein cholesterol (LDL-C), Very Low density lipoprotein cholesterol (VLDL-C), triglycerides (TG), Fasting blood glucose were 183.7 (32.9), 38.12 (7.59), 104.4 (29.42), 31.66 (13.09), 158.44 (65.61), 95.9(9.9) mg/dl respectively. The statistical analysis showed that the difference in the above values between cases and controls was significant and all the mean values except HDL-C were increased in cases. Conclusions: Hypothyroid patients demonstrate significant increase in serum lipids as compared to healthy individuals. More females are diagnosed with hypothyroidism and dyslipidemia is associated with primary hypothyroidism.